Experimental and Numerical Study of Dynamics of Premixed Hydrogen-Air Flames Propagating in Ducts - Xiao, Huahua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This thesis offers important new insights into and a deeper understanding of premixed flame instabilities and hydrogen safety. Further, it explains the underlying mechanisms that control the combustion processes in tubes. The author's previous scientific accomplishments, which include a series of high-quality publications in the best journals in our field, Combustion and Flame and International Journal of Heat and Mass Transfer, are very impressive and have already made a significant contribution to combustion science.
Background and Introduction -- Experiments of Premixed Hydrogen-Air Flame Propagation in Ducts -- Numerical Simulations of Dynamics of Premixed Hydrogen-Air Flames Propagating in Ducts -- Theoretical Analysis of Premixed Hydrogen-Air Flame Propagation in Ducts -- Mechanisms of Flame Deformations in Premixed Hydrogen-Air Flame Propagation -- Conclusions and Futher Work.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Continuum mechanics; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Continuum Mechanics